(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Wireless sensor networks improve systems for home automation, healthcare, temperature management, energy consumption monitoring, and other applications. This article focuses on a temperature control system for residential, educational, industrial, and commercial buildings, among other applications. Using ZigBee-based wireless sensor networks, we offer a framework for interior temperature control and optimization. The system’s architectural architecture as well as implementation recommendations are discussed in this article. The suggested system promotes energy-saving techniques that reduce the number of data transfers throughout the network. The framework also investigates methods for localization, such that algorithms that control temperature settings may utilize the nodes’ position. Wireless sensing networking have been a developing field of study and innovation due to the large amount of industries that may considerably profit form these solutions. This has lead to the creation of sensing networks or "motes," which are small, low cost, disposable, and personality device processors that can collect input from a connected sensor, analyse the data, and broadcast the findings. Despite the fact that like sensor networks are possible, the sensors’ very wireless nature poses a variety of security risks when used for specific purposes such as military, surveillance, and so on.